The Impact of Accounting Restatements on the Cost of Equity Capital in Emerging Markets: Evidence from Kingdom of Saudi Arabia - Saad Saad Raad Faysal; Ali Saad Mohammed; Tamanna Dalwai (PT. Radja Intercontinental Publishing, 2024)
This study examines the role of accounting re-statement in increasing the cost of equity capital in emerging markets in the Kingdom of Saudi Arabia (KSA). This study is located from 2009 to 2019 with 116 firms and 1276 firm-year observations in the Saudi Stock Exchange. The authors used a least-squares regression model to verify the study variables; according to the panel data tests, the Fixed effects (Robust FE) had preferred in our model. The findings show that the re-statement has a positive significance on the cost of equity capital; these results indicate that an increase in the frequency of the re-statement increases the cost of equity capital and vice versa. Moreover, our results indicate a significant relationship between financial leverage and the cost of equity capital; this means the investors demand significant returns in companies that have frequently practiced re-statement, and this is consistent with the arguments that an increase in re-statement increases the cost of equity capital in the Saudi Stock Exchange. The results can benefit The Saudi Arabia Accounting Standards Committee (KSASC) and KSA Vision 2030. These results are significant to investors and financial policymakers in the KSA. So, it is essential to improve the economy and avoid a financial crisis in the future. Although the contribution is limited, it will provide a helpful guide for seriously considering new procedures that include narrow limitations in re-statement to reduce the opportunistic behavior of managers.